Pengaruh media sosial terhadap kesehatan mental mahasiswa: Analisis risikio dan upaya pencegahan - Setyawan, Ardi Dwi (Maliki Interdisciplinary Journal, 2025)
The increasing use of social media among students has a significant impact on their mental health. While social media can support communication and provide access to information, its negative effects, such as anxiety, depression, sleep disorders, and social media addiction, have become increasingly noticeable. The phenomenon of social comparison, which is common on social media, adds psychological pressure, making students feel inferior and dissatisfied with themselves. Social media addiction also disrupts sleep patterns and reduces the quality of social interactions, potentially worsening mental health. This article analyzes the influence of social media on students’ mental health, identifies risk factors such as excessive usage duration and exposure to negative content, and offers preventive measures through increased digital literacy. By understanding these impacts, students can use social media more wisely to support their psychological well-being. The increasing use of social media among students has a significant impact on their mental health. While social media can support communication and provide access to information, its negative effects, such as anxiety, depression, sleep disorders, and social media addiction, have become increasingly noticeable. The phenomenon of social comparison, which is common on social media, adds psychological pressure, making students feel inferior and dissatisfied with themselves. Social media addiction also disrupts sleep patterns and reduces the quality of social interactions, potentially worsening mental health. This article analyzes the influence of social media on students’ mental health, identifies risk factors such as excessive usage duration and exposure to negative content, and offers preventive measures through increased digital literacy. By understanding these impacts, students can use social media more wisely to support their psychological well-being. The increasing use of social media among students has a significant impact on their mental health. While social media can support communication and provide access to information, its negative effects, such as anxiety, depression, sleep disorders, and social media addiction, have become increasingly noticeable. The phenomenon of social comparison, which is common on social media, adds psychological pressure, making students feel inferior and dissatisfied with themselves. Social media addiction also disrupts sleep patterns and reduces the quality of social interactions, potentially worsening mental health. This article analyzes the influence of social media on students’ mental health, identifies risk factors such as excessive usage duration and exposure to negative content, and offers preventive measures through increased digital literacy. By understanding these impacts, students can use social media more wisely to support their psychological well-being.